2022
DOI: 10.3390/jcm11195822
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Race on Acute Kidney Injury

Abstract: Racial disparities in incidence and outcomes of acute kidney injury (AKI) are pervasive and are driven in part by social inequities and other factors. It is well-documented that Black patients face higher risk of AKI and seemingly have a survival advantage compared to White counterparts. Various explanations have been advanced and suggested to account for this, including differences in susceptibility to kidney injury, severity of illness, and socioeconomic factors. In this review, we try to understand and furt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 81 publications
0
4
0
Order By: Relevance
“…The higher probability of AKI occurrence in London might be linked to the larger representation of males and individuals from ethnic minority backgrounds in its population. Both of these factors have been connected to an elevated risk of developing AKI [33,34]. The lower mortality rate observed in London can be attributed to the presence of a younger population and a diverse ethnic composition.…”
Section: Discussionmentioning
confidence: 99%
“…The higher probability of AKI occurrence in London might be linked to the larger representation of males and individuals from ethnic minority backgrounds in its population. Both of these factors have been connected to an elevated risk of developing AKI [33,34]. The lower mortality rate observed in London can be attributed to the presence of a younger population and a diverse ethnic composition.…”
Section: Discussionmentioning
confidence: 99%
“…Major risk factors for AKI development are sepsis, hypovolemia, Chronic Kidney Disease (CKD) and diabetes mellitus [ 56 ]. The black race has an increased risk of AKI occurrence, which seem to be related to a direct interaction between genetic, as well as clinical and social class, factors [ 57 ]. Its pathophysiology consists of a complex multifactorial process [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, the incidence of AKI varied across races and our study is the first to report the incidence of AKI in Asians in a large PJI cohort. Reports from other areas have shown that black patients tend to have a higher risk of AKI than white patients, and Asians also have a relatively low incidence of AKI ( Hassan and Balogun, 2022 ). However, black patients with AKI would have a lower in-hospital mortality rate ( Hassan et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%